A Study on the Role of the KITARecycle app in Enhancing Waste Separation and 3R Practice in Higher Educational Institutions in Malaysia - Lim, Nicole May Lynn; Binti Ali, Roslinda; Bin Jailani, Mohammad Asraff (Progress in Engineering Application and Technology, 2025)
The municipal solid waste generation rate in Malaysia has risen over the years. This situation must be controlled to prevent impacts on human health and the environment. One of the many ways to address this issue is by practising waste separation and 3R as a daily routine. This research investigates the role of the KITARecycle app in promoting waste management practices among tertiary education staff and students in Malaysia. A questionnaire survey is distributed to the respondents via the KITARecycle app. The questionnaire consisted of 4 parts, which include i) demographic profile, ii) knowledge, attitude and behaviour towards waste segregation and 3R, and iii) the feedback on the KITARecycle app. The results obtained from the questionnaire were analysed using the Statistical Package for the Social Sciences (SPSS), employing descriptive statistics, cross-tabulation analysis and correlation tests. When correlating gender and overall satisfaction on the app, no significant relationship is found between the two variables. However, a cross-tabulation analysis has shown that female has higher overall satisfaction than male. The findings show that the KITARecycle app has improved the knowledge of users in separation at source and 3R. This could be related to the app providing a list of the materials accepted for recycling, which has indirectly instilled knowledge on the recyclability of the materials. Furthermore, the app has also positively influenced the attitude and behaviour of users. This could be the outcome of providing monetary incentives to the users when they separate their waste, which can be a strong influence in shaping positive attitudes and behaviors of users.